Zarys „problematyki chłopskiej” w Rumunii przed 1914 rokiem - Dubicki, Andrzej (Zeszyty Wiejskie, 2011)
The so-called „peasant cause” was characteristic for Kingdom of Romania in the late 19th and early 20th century. It was based upon the late development of serfdom in Romanian principalities of Wallachia and Moldavia, which became popular only about 1820 in connection with new trade possibilities, allowing the direct export of grain and other agricultural goods to the Western Europe. Earlier it was possible only with Ottoman agency which was naturally unprofitable. “Peasant cause” became extremely actual after the Union of both principalities in 1861, and since this time has been often connected with question of “popular vote”. The first, but limited agricultural reform took place in 1864, and again was extended in 1889 as an answer for peasant uprising. Finally both questions: agricultural and voting were concluded after the Great War in 1919 (introduction of popular vote), and 1921 (final agricultural reform in Romania).